La « communauté de marque » comme accomplissement pratique - Julia Velkovska (Communication)
Based on a video-ethnographic study of a cell phone company’s customer service department, the author explores the practices of web advisors and how the introduction of the notion of brand communities has transformed customer relationships. This notion is analyzed from a praxeological perspective as an enhancement of the advisors' main functions — writing and cooperation — for the purpose of creating, developing, and coordinating “digital customer communities”. The author brings together the sociology of internet use and the sociology of labour in order to observe the performativity of “brand community” in organizational settings, including the emergence of a cooperative model of customer relations.